2020
DOI: 10.1002/cctc.201901988
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Catalysis for One‐pot Bis‐alkoxycarbonylation of Terminal Alkynes over Pd/Xantphos−Al(OTf)3 Bi‐functional Catalytic System

Abstract: Tandem bis‐alkoxycarbonylation of alkynes allows for the preparation of 2‐substituted succinates from alkynes and nucleophile alcohol via two successive alkoxycarbonylation with advantages of 100 % atomic economy and simplified one‐pot operation. Herein, the one‐pot tandem bis‐alkoxycarbonylation of alkynes was accomplished over the bi‐functional catalytic system containing Xantphos‐modified Pd‐complex and Lewis super‐acid of Al(OTf)3. It was found that, via the synergetic catalysis, the involved Xantphos‐modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…This observation suggested that Al (OTf) 3 coordinated with the oxygen atom in the hydroxyl group and led to the cleavage of the O‐H bond in MeOH and the release of the proton. This process might facilitate the formation of the [Pd II ‐H] + reactive species 4,19,34 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation suggested that Al (OTf) 3 coordinated with the oxygen atom in the hydroxyl group and led to the cleavage of the O‐H bond in MeOH and the release of the proton. This process might facilitate the formation of the [Pd II ‐H] + reactive species 4,19,34 …”
Section: Resultsmentioning
confidence: 99%
“…Notably, compounds such as dimethyl succinate (DMS), dimethyl adipate, and other diesters have been the research hotspots in today's academia and industry 2,3 . Dimethyl succinate (DMS) can be used as a food mold inhibitor and biodegradable environmentally friendly plastic (PBS) 4–6 . Additionally, it can be used in the synthesis of miglitazone analogs, known for their therapeutic efficacy against type II diabetes 7 ; On the other hand, dimethyl adipate was the fundamental component in polyamide and polyester, finding applications in the manufacturing of plasticizers, lubricants, and nylons 8,9 …”
Section: Introductionmentioning
confidence: 99%
“…Chatani et al reported a Rh-catalyzed carbonylative cyclization of internal alkynes with 2-bromophenylboronic acids leading to indenones (Scheme 11). 37 The regioselectivity of this reaction was largely determined by the electronic and steric hindrance of substituents on alkynes. In general, a bulky group and an electron-withdrawing group prefer to stay at the αposition of the indenones.…”
Section: Intermolecular Carbonylative Multifunctionalization Of Alkynesmentioning
confidence: 99%
“…In addition, it also has a wide range of applications in industry (such as beverages, cosmetics) [32][33][34][35][36][37]. Accordingly, much effort has been devoted to developing new synthetic methods to establish such a structure (Scheme 1B) [38][39][40][41][42][43][44][45][46][47][48][49][50]. For example, Chatani and co-workers accomplished a Rh-catalyzed alkoxycarbonylation of internal alkynes to construct saturated succinates by using special alcohol, pyridine-2-ylmethanol [40].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%